Sistema para el seguimiento de auditorías técnicas de vías y puentes - Mora-Cordero, Eduardo Vinicio (Instituto Tecnológico de Costa Rica, 2014)
Through this project, it is intended that the reader knows about the processes that involve technical audits in Costa Rica, since its meaning to completion with due publication of information on the website by the National Roads Authority (Consejo Nacional de Vialidad), Department Conservation Roads and Bridges. The process is focused on the improvement and implementation of tools for monitoring the technical audits and review quality processes to works studied. Standard parameters of visited items were acquired through technical tours, along with a methodology that is part of quality control both individual and group level, which facilitates the management of technical audits. The study of cases in different regions of the country, with the implementation of new tools, shows a high degree of reliability and simplicity, which seeks to generate knowledge in the reader about those procedures associated with a project, while minimizing gaps in around the monitoring and management of technical processes related to roads and bridges in the country. It is the duty of the public institution reporting and methodologies available to the general public, to publicize the work performed on projects of national interest, as a consequence, such tools, which come is created to provide transparency in the processes public.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2014.
Keywords: Procesos; Consejo Nacional de Vialidad; Mejoramiento; Control de calidad; Conservación de vías